answersLogoWhite

0

-5x -23 + 3x = -27

Combine like terms:

-2x - 23 = -27

Add 23 to each side:

-2x = -4

Divide each side by -2:

x = -4/-2

x = 2

User Avatar

Wiki User

13y ago

Still curious? Ask our experts.

Chat with our AI personalities

JordanJordan
Looking for a career mentor? I've seen my fair share of shake-ups.
Chat with Jordan
RafaRafa
There's no fun in playing it safe. Why not try something a little unhinged?
Chat with Rafa
BeauBeau
You're doing better than you think!
Chat with Beau

Add your answer:

Earn +20 pts
Q: -5x - 23 plus 3x equals -27?
Write your answer...
Submit
Still have questions?
magnify glass
imp